Enseñanza aprendizaje de la geometría a través de las transformaciones en el plano en los estudiantes del grado quinto - Romero Santiago, Ángel Leandro (Universidad Antonio Nariño, 2022)
Geometry as a branch of mathematics has multiple uses and plays an important role in the development of mathematical thinking. Despite the use of didactic resources and new technologies in its teaching and learning process, difficulties persist in students’ learning. To resolve these limitations, it is proposed geometry teaching and learning through geometric transformations to strengthen students’ geometric thinking. The research aims to promote teaching and learning process of plane geometry through transformations in the plane with fifth grade students from the Institución Educativa Departamental Bicentenario in Funza